2021
DOI: 10.1038/s41598-021-88617-6
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA analysis portal is a next-generation tool for exploring and analyzing miRNA-focused data in the literature

Abstract: MicroRNAs constitute a class of noncoding small RNAs involved in the posttranscriptional regulation of many biological pathways. In recent years, microRNAs have also been associated with regulation across kingdoms, demonstrating that exogenous miRNAs can function in mammals in a fashion similar to mammalian miRNAs. The growing interest in microRNAs and the increasing amount of literature and molecular and biomedical data available make it difficult to identify records of interest and keep up to date with novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Until 2019, the miRBase database (miRBase Release 22.1, https://www.mirbase.org/) reported entries of 38 589 miRNAs in 271 species, including 2654 mature human miRNAs (91). Increasing evidence supports the significant roles of miRNAs in regulating the mechanisms responsible for the pathophysiology of numerous diseases, including cardiovascular diseases, obesity, different types of cancer, and diabetes (73,(92)(93)(94)(95)(96)(97)(98).…”
Section: Mirnas In Diabetic Cardiomyopathymentioning
confidence: 98%
“…Until 2019, the miRBase database (miRBase Release 22.1, https://www.mirbase.org/) reported entries of 38 589 miRNAs in 271 species, including 2654 mature human miRNAs (91). Increasing evidence supports the significant roles of miRNAs in regulating the mechanisms responsible for the pathophysiology of numerous diseases, including cardiovascular diseases, obesity, different types of cancer, and diabetes (73,(92)(93)(94)(95)(96)(97)(98).…”
Section: Mirnas In Diabetic Cardiomyopathymentioning
confidence: 98%
“…Alternatively, miRNAs, by silencing one specific pathway, can up-regulate the transcription of certain target mRNAs that control the target genes [ 17 ]. According to a recent estimate, 60% of all protein-encoding genes are regulated by miRNAs [ 18 ]. Intricate studies of miRNA functions have revealed that a single miRNA can potentially target numerous mRNAs, whereas one mRNA can be targeted by multiple miRNAs, reflecting the complexity of gene expression regulation [ 19 ].…”
Section: Mirnas Evs and Physical Barriersmentioning
confidence: 99%
“…The roles of micro-ribonucleic acids (miRs) in disease development are increasingly the subject of biobehavioral research ( 1 ). MiRs are small, single-stranded, non-coding ribonucleic acids (RNAs) between 17 and 25 nucleotides in length that operate at the post-transcriptional level to regulate gene expression ( 2 ).…”
Section: Introductionmentioning
confidence: 99%